Consumption of vegetables and fruits and risk of breast cancer. - Gils, v; Peeters, P; Bueno-de-Mesquita, H; Boshuizen, H; Lahmann, P; Clavel-Chapelon, F; Thiébaut, A; Kesse, E; Sieri, S; Palli, D; Tumino, R; Panico, S; et al. (2005)
CONTEXT: The intake of vegetables and fruits has been thought to protect against breast cancer. Most of the evidence comes from case-control studies, but a recent pooled analysis of the relatively few published cohort studies suggests no significantly reduced breast cancer risk is associated with vegetable and fruit consumption. OBJECTIVE: To examine the relation between total and specific vegetable and fruit intake and the incidence of breast cancer. DESIGN, SETTING, AND PARTICIPANTS: Prospective study of 285,526 women between the ages of 25 and 70 years, participating in the European Prospective Investigation Into Cancer and Nutrition (EPIC) study, recruited from 8 of the 10 participating European countries. Participants completed a dietary questionnaire in 1992-1998 and were followed up for incidence of cancer until 2002. MAIN OUTCOME MEASURES: Relative risks for breast cancer by total and specific vegetable and fruit intake. Analyses were stratified by age at recruitment and study center. Relative risks were adjusted for established breast cancer risk factors. RESULTS: During 1,486,402 person-years (median duration of follow-up, 5.4 years), 3659 invasive incident breast cancer cases were reported. No significant associations between vegetable or fruit intake and breast cancer risk were observed. Relative risks for the highest vs the lowest quintile were 0.98 (95% confidence interval [CI], 0.84-1.14) for total vegetables, 1.09 (95% CI , 0.94-1.25) for total fruit, and 1.05 (95% CI , 0.92-1.20) for fruit and vegetable juices. For 6 specific vegetable subgroups no associations with breast cancer risk were observed either. CONCLUSION: Although the period of follow-up is limited for now, the results suggest that total or specific vegetable and fruit intake is not associated with risk for breast cancer.